Takaful narrative: a study on women with gynaecological diseases and mental health in Malaysia - Tajul Urus, Nur Sarah; Md Aziz, Mu’azah; Burhanuddin, Iswandi Harahap; Md Noor, Mohamad Lukman Al Hakim; Salleh, Mohd Muslim (Abrar Global, 2024)
Takaful is a self-protection system that ensures the safety and well-being of its members. Although the takaful sector has existed in Malaysia since 1982, it does not highlight the issues that women frequently experience in terms of gynaecological and mental diseases. Gynaecological sickness is a common condition among women, whereas mental illness occurs in some women who are subjected to emotional stress, sentiments, and workload. Both of these issues are not addressed in takaful systems. This article addresses the takaful protection system for gynaecological and mental patients, which has not been fully polished by Malaysia's personal protection system, particularly the takaful industry based on Sharia and legal analysis. This study is a library study designed to identify women with gynaecological and mental illnesses in Malaysia, allowing the researcher to function as a simulated observer and gain experience with women with gynaecological and mental illnesses in Malaysia. This analysis is based on manuscripts from newspaper stories, journal papers, books about women's gynaecology and mental health, theses, and related articles that review the study's findings. Accordingly, takaful firms do not cover gynaecological or mental illnesses that donors may face. Therefore, takaful companies need to offer this scheme by taking social responsibility into account for contributors who suffer from gynaecological and mental problems, especially for less able women, by taking a compassionate approach under the takaful wa ta’awun ‘ala al birri wa al-taqwa.